2012
DOI: 10.1038/npp.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of Cannabinoids in Anxiety Responses: CB1 and GABAB Receptors in the Balance of GABAergic and Glutamatergic Neurotransmission

Abstract: Biphasic effects of cannabinoids have been shown in processes such as feeding behavior, motor activity, motivational processes and anxiety responses. Using two different tests for the characterization of anxiety-related behavior (elevated plus-maze and holeboard), we first identified in wild-type C57BL/6N mice, two doses of the synthetic CB1 cannabinoid receptor agonist CP-55,940 with anxiolytic (1 mg/kg) and anxiogenic properties (50 mg/kg), respectively. To clarify the role of CB1 receptors in this biphasic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
198
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(230 citation statements)
references
References 48 publications
24
198
0
4
Order By: Relevance
“…APICA administration dose-dependently decreased total distance traveled in the open field test, This result is consistent with preliminary evaluation of APICA cannabinomimetic profile, which showed that APICA dose-dependently induced hypothermia and reduced heart rate at the maximal dose of 10 mg/kg, a similar potency as Δ 9 -THC, but lower than JWH-018, the representative member of cannabinomimetic indoles [4]. Since CB1 agonists have been shown to exert anxiogenic effect [13], we also evaluated APICA activity on behavioural reactivity in the open field. Our results show that APICA strongly decreased the time spent in the center of the arena, as well as the number of transitions in the central area, and this observation is consistent with an overall reduction of locomotor activity and exploration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…APICA administration dose-dependently decreased total distance traveled in the open field test, This result is consistent with preliminary evaluation of APICA cannabinomimetic profile, which showed that APICA dose-dependently induced hypothermia and reduced heart rate at the maximal dose of 10 mg/kg, a similar potency as Δ 9 -THC, but lower than JWH-018, the representative member of cannabinomimetic indoles [4]. Since CB1 agonists have been shown to exert anxiogenic effect [13], we also evaluated APICA activity on behavioural reactivity in the open field. Our results show that APICA strongly decreased the time spent in the center of the arena, as well as the number of transitions in the central area, and this observation is consistent with an overall reduction of locomotor activity and exploration.…”
Section: Discussionsupporting
confidence: 87%
“…These opposite observations might be explained by the distribution of CB1 receptors in the brain. Rey et al [13] showed a biphasic effects of the synthetic CB1 cannabinoid receptor agonist CP-55,940, demonstrating that the anxiogenic effect exerted by the high doses was mediated via the CB1 receptor activation on the GABAergic terminals. Indeed, the broad distribution of CB1 receptors in the central nervous system [17], together with its modulatory role on neurotransmission [18], account for the controversial activity of cannabinoids on anxiety modulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This PK −/− /Tau vlw model showed an elevated level of self-injured wounds on the front of the face, due to their compulsive behavior and repetitive selfscratching [25]. The role of cannabinoids in mood and anxiety disorders has been described [34][35][36]. Each mouse was recorded to evaluate the extent of facial barbering in the different groups of the experiment.…”
Section: Self-injurious Behaviormentioning
confidence: 99%
“…The nucleic acids were dissolved in 150 l of sterile water. For PCR, 150 ng of genomic DNA was denatured for 3 min at 94 • C and subjected to 35 Twenty-microliter volumes of PCR products were analyzed by electrophoresis on a 1.8% agarose gel that was subsequently stained with ethidium bromide for visualization of DNA bands. DNA molecular weight markers (Roche, Spain) were used to provide a size reference for the test reactions [25,26].…”
Section: Genotype Determination By Pcrmentioning
confidence: 99%